Peran Transparansi dan Akuntabilitas dalam MeningkatkanTata Kelola Perusahaan yang Baik (GCG) pada PT Astra Agro Lestari Tbk. - Yoga Salim Putra; Youlanda Melanie Putri; Dhea Amanda Khoirunisa (Jurnal Riset Multidisiplin Edukasi, 2025)
The purpose of this study is to analyze the implementation of good corporate governance at PT Astra Agro Lestari Tbk, focusing on aspects of transparency and accountability. The approach used in this research uses a qualitative descriptive method. Data collected based on literature studies and secondary document analysis in the form of annual reports, sustainability reports, as well as journals and regulations related to GCG used in this company. The assessment was conducted using a scorecard instrument based on indicators, parameters, and test factors. The results showed that the company's transparency was categorized as excellent (score 85.85%), while accountability was classified as good (score 75.5%). Transparency is the most dominant aspect in supporting the implementation of GCG, while accountability still needs to be improved, especially in the aspects of internal evaluation audits and reporting. It is recommended that companies strengthen audit documentation and reporting systems, while further research can examine other GCG principles to obtain more comprehensive results.